2019
DOI: 10.1134/s1063778819090114
|View full text |Cite
|
Sign up to set email alerts
|

The Hoyle State in the Relativistic Dissociation of Light Nuclei

Abstract: In the context of the search for triples of relativistic α-particles in the Hoyle state, the analysis of available data on the dissociation of the nuclei 12 C, 16 O and 22 Ne in the nuclear emulsion was carried out. The Hoyle state is identified by the invariant mass calculated from pair angles of expansion in α-triples in the approximation of the conservation of the momentum per nucleon of the parent nucleus. The contribution of the Hoyle state to the dissociation of 12 C → 3α is 11%. In the case of the coher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This data set includes precision measurements of the emission angles of relativistic from 2 to 5α particles, which allowed one to analyse variables. It has been found that the probability of identifying the 8 Be, 9 B and HS states grows with the multiplicity of α particles in the event [15]. A similar result was obtained by analysing 1093 events of nα fragmentation of 28 Si nuclei with the energy of 14.6 GeV/nucleon in NTE up to 6α particles in the event [14].…”
Section: Alpha Partial Dissociation Of Heavy Relativistic Nucleisupporting
confidence: 65%
See 1 more Smart Citation
“…This data set includes precision measurements of the emission angles of relativistic from 2 to 5α particles, which allowed one to analyse variables. It has been found that the probability of identifying the 8 Be, 9 B and HS states grows with the multiplicity of α particles in the event [15]. A similar result was obtained by analysing 1093 events of nα fragmentation of 28 Si nuclei with the energy of 14.6 GeV/nucleon in NTE up to 6α particles in the event [14].…”
Section: Alpha Partial Dissociation Of Heavy Relativistic Nucleisupporting
confidence: 65%
“…Starting with the fragmentation of 16 O nuclei in the energy range from the 3.65 to 200 GeV/nucleon, the analysis has shown a relative increase in the contribution of 8 Be nuclei with the growing number of relativistic α particles per event [14]. The results of measurements of 4301 interactions of 22 Ne nuclei at the energy of 3.22 A GeV were analyzed in [15]. This data set includes precision measurements of the emission angles of relativistic from 2 to 5α particles, which allowed one to analyse variables.…”
Section: Alpha Partial Dissociation Of Heavy Relativistic Nucleimentioning
confidence: 99%